Adoption of farm mechanization, cropland expansion, and intensification in Ghana - Houssou, Nazaire; Chapoto, Antony (International Association of Agricultural Economists, 2015)
This research assesses whether the recent public and private efforts to improve farmer’s access to mechanical power in Ghana, have had their intended effects on the country’s agricultural sector. Using panel survey data, this paper analyzes the impacts of mechanization on cropland expansion and farming system intensification in Northern Ghana. Findings show a positive correlation between farm mechanization and cropland expansion during the survey period. However, there was no evidence of increasing farm input use with the use of tractors. Indeed, findings seem to suggest an inverse relationship between mechanization and farm intensification. We conclude that tractorization is unlikely to foster farm input intensification in regions such as Northern Ghana where farmlands are still abundant. Houssou, Nazaire; Chapoto, Anthony